CONTEMPORARY SIGNIFICANCE OF THE NAAT OF HAFEEZ TAYEB (THE NEED AND IMPORTANCE OF HAFEEZ TAIB’S NAAT IN THE PRESENT AGE WITH RESPECT TO INDIVIDUAL AND SOCIETY) - Dr. Razia Majeed; Dr. Tahir Abbas Tayib; Dr Aqsa Sajid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The importance of Hafeez Tayeb’s message at individual and collective levels adds to the contemporary significance of his naat. He sets the Prophet Muhammad (PBUH) as a standard for himself, and extends the circle of this standard from his person to the total universe. The mission of Prophet Muhammad (PBUH) is the success of entire humanity. A success that is not possible without the civilization of humanity. Islam brought the universal message of peace and prosperity. The welfare of this world and the hereafter is the responsibility of the enlightened religion of Islam. Therefore, the solution to the problems and challenges faced by humanity today should be found in "Practical Tafseer of the Qur’an”. Modern man needs to be told in an effective style that Muhammad (PBUH) is the perfect human being, whose pattern of life is a cure for the individual and collective sufferings. There is a great need to create awareness of the ascension of humanity in the forgotten Muslims as well as in the lost people in this age of chaos. It is not enough to say Kalma Tayyaba with the tongue, the heart and eyes must also be converted to Islam. If the lips are filled with love for the Messenger of Allah (PBUH) and the heart is not moistened with his love, it is not possible to create any kind of revolution at both the individual and collective levels. This is the real message of Hafeez Tayeb, which he has derived from the biography of the Prophet of the Islam, and then conveyed to us in the form of Naat. Therefore, the meaning of his naat increases even more in this period of tribulation. The revolutions of the time will be the reason to tell the extended meanings of Hafeez Tayeb’s naat.